2016
DOI: 10.1016/j.jallcom.2016.07.283
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of ZnO and manganese-doped ZnO

Abstract: The structural, morphological and optical properties of manganese oxides supported on commercial ZnO, prepared by impregnation with manganese nitrate, were investigated. The nominal compositions of Mn in the samples were 5, 10, 15 and 20 %w/w.The Xray diffraction (XRD) experiments revealed the presence of the ZnO wurtzite phase in all the samples, and ZnMnO 3 was also found in the samples with 15 wt% and 20 wt% of Mn. X-ray photoelectron spectroscopy (XPS) showed the presence of Mn 2+ and Mn 4+ in the xMnZnO s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The peaks of ZnO–SiO 2 -pH5.0 and ZnO–SiO 2 -pH7.0 at 1046.0 and 1045.5 eV correspond to Zn2p 1/2 orbital; the peaks at 1023.0 and 1022.5 eV correspond to the Zn2p 3/2 orbital [ 26 ]. These peaks are equivalent to the 2p 1/2 and 2p 3/2 energy peaks (1044.2 and 1021.2 eV) of ZnO [ 27 ]. Moreover, the energy difference between Zn2p 1/2 and Zn2p 3/2 orbitals is 23 eV, which is the same as that of ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks of ZnO–SiO 2 -pH5.0 and ZnO–SiO 2 -pH7.0 at 1046.0 and 1045.5 eV correspond to Zn2p 1/2 orbital; the peaks at 1023.0 and 1022.5 eV correspond to the Zn2p 3/2 orbital [ 26 ]. These peaks are equivalent to the 2p 1/2 and 2p 3/2 energy peaks (1044.2 and 1021.2 eV) of ZnO [ 27 ]. Moreover, the energy difference between Zn2p 1/2 and Zn2p 3/2 orbitals is 23 eV, which is the same as that of ZnO.…”
Section: Resultsmentioning
confidence: 99%
“…It appeared that Sn 2+ - doped ZnO QDs still maintained the main phase of ZnO, which was different from those of the Sn-doped ZnO NPs with a high Sn concentration [24][25][26] but was the same as that of the Sb doped ZnO with a low Sb concentration. 27 The interplanar spacing increased with increasing Sn 2+ concentration. This was similar to the trend in the calculated cell parameters of Zn 1Àx Sn x O, as shown in Table 1.…”
Section: Measurementmentioning
confidence: 93%
“…All the data were corrected with respect to the standard peak of C 1s at 284.6 eV. [27][28][29][30] As shown in Fig. 4, for all the samples, both Sn and Zn peaks could be found in the XPS spectra.…”
Section: Measurementmentioning
confidence: 99%
“…Figure 3c showed that Mg1s XPS peak from Mg 2+ oxides at 1303-1305 eV for Mg loaded ZSM-5 zeolites [34]. The 2p XPS peak for Zn loaded ZSM-5 zeolites was located at 1021-1025 eV [35], associated to Zn 2+ oxides ( Figure 3d). The contents of Mg or Zn on NaZSM-5(120), NaZSM-5(45) and NaZSM-5(31) were 6.7 wt% or 5.9 wt%, 8.7 wt% or 9.5 wt%, and 5.6 wt% or 5.1 wt%, respectively, by XPS analysis.…”
Section: Characteristics Of Catalystsmentioning
confidence: 94%